Seroprevalence and trends of transfusion transmissible infections among voluntary and replacement donors–an institutional retrospective study - Dr. Santosh Meena; Dr. Veena Maheshwari; Dr. Deepti Gupta (Tropical Journal of Pathology and Microbiology, 2018)
Introduction:Transfusion transmitted infections are major problem associated with blood transfusion. There are several infectious as well as non-infectious risks associated with transfusion of blood. Aim andObjective:The present study was carried out to find out the sero-prevalence and changing trends of various TTIs in blood donors.Material andMethods:A record based study was conducted from January 2008- December 2010. Data were collected from therecords of blood bank which also included data of blood donation camps. Data regarding sex, screening testresults and type of donors were collected from the records.Results:Out of 17640 donors, voluntary donors (78.4%) were more in comparison to replacement donors (21.6%). Out of all TTIs, prevalence of HBV (2.14%) was highest followed by, HCV (0.66%), HIV (0.6%), Malaria (0.14%) and Syphilis (0.05%).TTIs were more prevalent in replacement donors than voluntary donors. The number ofvoluntary donors has fallen from 2008 -2010, but there is male preponderance in both voluntary and replacement donors.Conclusion:From results it has been concluded that prevalence of transfusion transmitted infection (HIV, HBV, HCV, VDRL, and malaria) was more in replacement donors in comparison to voluntary donors. With the implementation of strict donor selection criteria, use of sensitive screening tests and establishment of strict guidelines for blood transfusion it may be possible to reduce the incidence of transfusion transmitted infection in the Indian scenario.